2009
DOI: 10.1074/jbc.m808326200
|View full text |Cite
|
Sign up to set email alerts
|

Occupancy and Functional Architecture of the Pigment Binding Sites of Photosystem II Antenna Complex Lhcb5

Abstract: Lhcb5 is an antenna protein that is highly conserved in plants and green algae. It is part of the inner layer of photosystem II antenna system retained in high light acclimated plants. To study the structure-function relation and the role of individual pigments in this complex, we (i) "knocked out" each of the chromophores bound to multiple (nine total) chlorophyll sites and (ii) exchanged the xanthophylls bound to the three xanthophyll sites. The occupancy and associated energy of the pigment binding sites we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
80
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 39 publications
(92 citation statements)
references
References 65 publications
12
80
0
Order By: Relevance
“…Unfortunately, none of the mutants targeting Chls close to the L2 site was stable enough to allow fluorescence time-resolved measurements. However, in CP26 the absence of Chl 603 induces a large increase of the fluorescence yield of the complex (40). Considering that Chl 603 is located in close contact with the carotenoid in L2, it is likely that it is responsible for the quenching also in CP24.…”
Section: Role Of Individual Pigments In Light Harvesting and Photopromentioning
confidence: 99%
“…Unfortunately, none of the mutants targeting Chls close to the L2 site was stable enough to allow fluorescence time-resolved measurements. However, in CP26 the absence of Chl 603 induces a large increase of the fluorescence yield of the complex (40). Considering that Chl 603 is located in close contact with the carotenoid in L2, it is likely that it is responsible for the quenching also in CP24.…”
Section: Role Of Individual Pigments In Light Harvesting and Photopromentioning
confidence: 99%
“…The pigment binding of most of the complexes was studied with the use of mutation analysis. Mutations of the putative Chl-binding residues followed by in vitro reconstitution [90] has led to the production of complexes lacking individual chromophores, allowing the characterization of each chromophore in each binding site [91][92][93][94][95][96]. This analysis has revealed that the biochemical and spectroscopic properties of Chls in several of the binding sites are conserved across the Lhc family.…”
Section: Structure Of the Antenna Complexes Of Photosystem IImentioning
confidence: 99%
“…1) was reconstructed [126] using the crystal structures of PSII core [44] and LHCII [78]. For the minor antenna complexes, the structure of a monomer of LHCII was used while the pigment composition/occupancy was assigned based on the results of mutation analysis experiments on in vitro reconstituted complexes [91,92,95,96]. The model shows that LHCII S is connected directly with CP43 and that Chls 612/611 of one of the monomers are facing Chl 43 of CP43.…”
Section: Energy Transfer In the Grana Membranesmentioning
confidence: 99%
“…CP24, CP26, and CP29 complexes were refolded in vitro from apoproteins expressed in E. coli and chlorophylls a and b plus lutein only or a total carotenoid mix. The resulting complexes were characterized (Table 2) by having lutein in both carotenoid binding sites L1 and L2 (LL complexes), whereas in the control complexes, the L2 binding site could be occupied by lutein, violaxanthin, or neoxanthin (LNV complexes) (Pagano et al, 1998;Ruban et al, 1999;Ballottari et al, 2009), except for CP24, which cannot bind neoxanthin either in vivo or in vitro (Pagano et al, 1998). LHCII trimers were purified from the wild type or the chy1 chy2 lut5 mutant, which has lutein as the only xanthophyll (Fiore et al, 2006).…”
Section: Ta Spectroscopy Of Isolated Lhc Complexesmentioning
confidence: 99%